2023
DOI: 10.3390/nu15030576
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Severe Vitamin D Deficiency in Patients with Primary Sclerosing Cholangitis

Abstract: Vitamin D deficiency has been linked with adverse events in various liver diseases. The present study aimed to recognize the association between severe vitamin D deficiency and disease progression, hepatobiliary malignancies, liver-related mortality, and the need for liver transplantation in primary sclerosing cholangitis (PSC). Patients with a diagnosis of PSC (n = 354), followed by the autoimmune liver disease clinic at the University of Alberta, were included. Patients with vitamin D levels < 25 nmol/L w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is known that the liver plays a pivotal role in the activation of vitamin D [ 58 ], and vitamin D regulates bone mineralization and absorption to maintain BMD [ 59 ]. However, patients with PSC are prone to severe vitamin D deficiency [ 60 , 61 ], suggesting that osteoporosis induced by PSC may be a type of hepatic osteodystrophy related to abnormal liver vitamin D metabolism. In addition, the liver is a central hub for lipid metabolism, and high blood lipid levels can induce the accumulation of lipids in cartilage, leading to osteoarthritis [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the liver plays a pivotal role in the activation of vitamin D [ 58 ], and vitamin D regulates bone mineralization and absorption to maintain BMD [ 59 ]. However, patients with PSC are prone to severe vitamin D deficiency [ 60 , 61 ], suggesting that osteoporosis induced by PSC may be a type of hepatic osteodystrophy related to abnormal liver vitamin D metabolism. In addition, the liver is a central hub for lipid metabolism, and high blood lipid levels can induce the accumulation of lipids in cartilage, leading to osteoarthritis [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may cause detrimental effects on the patient’s overall health, including impaired bone mass acquisition, rickets, and immune, cardiovascular, and respiratory system dysfunction [ 9 ]. Several previous studies reported that the severity of vitamin D deficiency in patients with cholestasis was associated with poor clinical outcomes, including incomplete response to ursodeoxycholic acid, cirrhosis development, liver-related mortality, and the need for liver transplantation [ 18 – 22 ].…”
Section: Introductionmentioning
confidence: 99%